2011
DOI: 10.1158/0008-5472.can-10-4058
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 and mTORC2 Regulate EMT, Motility, and Metastasis of Colorectal Cancer via RhoA and Rac1 Signaling Pathways

Abstract: Activation of phosphatidylinositol 3-kinase (PI3K)/Akt signaling is associated with growth and progression of colorectal cancer (CRC). We have previously shown that the mammalian target of rapamycin (mTOR) kinase, a downstream effector of PI3K/Akt signaling, regulates tumorigenesis of CRC. However, the contribution of mTOR and its interaction partners towards regulating CRC progression and metastasis remains poorly understood. We found that increased expression of mTOR, Raptor and Rictor mRNA was noted with ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
391
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 496 publications
(417 citation statements)
references
References 22 publications
25
391
1
Order By: Relevance
“…Our results presented here strongly suggest that the defect in mTORC1 signaling resulting from dysregulation of the MID1/PP2A axis is one of the avenues leading to OS pathogenesis. Of note, malformations occurring in OS patients have been attributed to defective migration patterns of neural crest cells needed to mediate ventral midline tissue formation in a very specific time window during development (1), and mTORC1 signaling not only is responsible for cytoskeleton dynamics and intracellular transport-both processes that significantly influence the migration potential of cells-but also has a direct regulatory function in migrating cells (52,53). Dysfunctional mTORC1 signaling in OS patients with MID1 mutations is therefore likely to significantly contribute to the OS phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Our results presented here strongly suggest that the defect in mTORC1 signaling resulting from dysregulation of the MID1/PP2A axis is one of the avenues leading to OS pathogenesis. Of note, malformations occurring in OS patients have been attributed to defective migration patterns of neural crest cells needed to mediate ventral midline tissue formation in a very specific time window during development (1), and mTORC1 signaling not only is responsible for cytoskeleton dynamics and intracellular transport-both processes that significantly influence the migration potential of cells-but also has a direct regulatory function in migrating cells (52,53). Dysfunctional mTORC1 signaling in OS patients with MID1 mutations is therefore likely to significantly contribute to the OS phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we expected that the non-metastatic character of hamartomas from brain samples could be related to the hyperphosphorylation of CTNND-1 S268. Previous studies showed that elevated mTORC1 and mTORC2 activity played a role in regulating the epithelialmesenchymal transition (EMT), motility and metastasis of colorectal cancer (21). It has also been shown that CTNND1 P-S268 is an E-cadherin-associated protein that modulates E-cadherin function and stability (20).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of phosphatidylinositol 3-kinase (PI3K)/ Akt signaling through activating mutations in PI3KCA or loss of PTEN is associated with the progression of CRC (Roy et al, 2002). Gulhati et al (2011) have previously shown that the mammalian target of rapamycin (mTOR) kinase, a downstream effector of PI3K/Akt signaling, could regulate the tumorigenesis of CRC. Their recent findings support a role for elevated mTORC1 and mTORC2 activity in regulating EMT and metastasis of CRC.…”
Section: Recently Demonstrated the Inhibitory Effect Roles Of Epithelmentioning
confidence: 99%